Cultural humility: Conclusion to the special issue. Issue 3 (September 2019) - Davis, Don E.; Hook, Joshua N.
We conclude the special issue by addressing some ongoing limitations within scholarship on humility and cultural humility that ought to temper our reading of the extant literature. We also discuss four critiques of initial scholarship in this area. We end with some suggestions for future research on cultural humility.